2016
DOI: 10.1021/acs.jchemed.5b00610
|View full text |Cite
|
Sign up to set email alerts
|

The Alcohol Dehydrogenase Kinetics Laboratory: Enhanced Data Analysis and Student-Designed Mini-Projects

Abstract: A highly instructive, wide-ranging laboratory project in which students study the effects of various parameters on the enzymatic activity of alcohol dehydrogenase has been adapted for the upper-division biochemistry and physical biochemistry laboratory. Our two main goals were to provide enhanced data analysis, featuring nonlinear regression, and also to give students experience in experimental design. Students use appropriate kinetic and thermodynamic equations to fit their data from Michaelis–Menten plots, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…(3) we can predict that [S] = = 5.7 mM. Using typical laboratory values for YADH in buffer , Fig. shows how the crowder glucose should alter enzyme activity above and below 5.7 mM ethanol.…”
Section: Macromolecular Crowdingmentioning
confidence: 96%
See 3 more Smart Citations
“…(3) we can predict that [S] = = 5.7 mM. Using typical laboratory values for YADH in buffer , Fig. shows how the crowder glucose should alter enzyme activity above and below 5.7 mM ethanol.…”
Section: Macromolecular Crowdingmentioning
confidence: 96%
“…To exemplify the effect of a specific crowder on a well‐characterized enzyme, Schneider et al showed in their first figure that glucose (300 g/L) lowered the K m (EtOH) value of yeast alcohol dehydrogenase (YADH) by about fivefold (from 17 mM to 3.4 mM) and V max by about 2.5‐fold; under these conditions, using Eq. (3) we can predict that [S] = = 5.7 mM.…”
Section: Macromolecular Crowdingmentioning
confidence: 99%
See 2 more Smart Citations
“…Hal ini menunjukkan bahwa penerapan (Rosa et al, 2018). Selain itu terdapat juga penelitian yang menyatakan bahwa kegiatan praktikum berbasis Mini Project dapat memberikan pengalaman eksperimen siswa (Silverstein, 2016).…”
Section: Penerapan Kegiatan Laboratorium Kimia Berbasis Mini Project unclassified